Comparison of Listening Mozart Music With Murotal Al Quran on the Pain of Hypertension Patients - Wirakhmi, Ikit Netra; Utami, Tin; Purnawan, Iwan (Jurnal Keperawatan Soedirman, 2018)
AbsstractThe number of people with hypertension is increasing over time. The most frequest complaint experienced by people with hypertension is pain. Complications of pain can be avoided through correct pain management. Listening to music and murotal Al Quran on some researches can provide a relaxation effect that potentially reduces pain. This study was aimed to identify differences effect in listening mozart music with murotal Al Quran in order to purifying pain of hypertensive sufferers. This research was quasi experiment with pre-test and post-test with two groups design. Data were collected using consecutive sampling technique with 15 respondents for each group. Pain measurement was taken twice before and after listening to music mozart or murotal Al Quran for 15 minutes. Statistic test using mann whitney showed that there was significant mean difference of pain before and after treatment in the murotal group of Al Quran (value p = 0,002). While in the mozart group the difference of pain before and after treatment was not significant (p = 0,051). Listening to murotal Al Quran is more effective in reducing pain in hypertensive sufferers compared to that in mozart music.AbstrakJumlah penerita hipertensi terus mengalmi peningkatan. Salah satu keluhan yang sering dialami oleh penderita hipertensi adalah rasa sakit. Komplikasi dari nyeri dapat dihindari melalui manajemen nyeri yang benar. Mendengarkan musik dan murotal Al Quran pada beberapa penelitian dapat memberikan efek relaksasi yang berpotensi mengurangi rasa sakit. Penelitian ini bertujuan untuk mengidentifikasi perbedaan dalam efek mendengarkan musik mozart dengan murotal Al Quran dalam memurnikan rasa sakit penderita hipertensi. Penelitian ini merupakan eksperimen semu dengan pre test dan post test dengan dua desain kelompok. Data dikumpulkan menggunakan teknik consecutive sampling dengan 15 responden untuk setiap kelompok. Data nyeri masing-masing responden diambil dua kali sebelum dan sesudah mendengarkan musik mozart atau murotal Al Quran selama 15 menit. Uji statistik menggunakan mann whitney menunjukkan bahwa ada perbedaan rerata nyeri sebelum dan sesudah perlakuan pada kelompok murotal Al Quran (nilai p = 0,002). Sedangkan pada kelompok mozart perbedaan nyeri sebelum dan sesudah perlakuan tidak signifikan (p = 0,051). Mendengarkan murotal Al Quran lebih efektif dalam mengurangi rasa sakit penderita hipertensi dibandingkan dengan musik mozart.